Pelatihan Metode System of Rice Intensification (SRI) Dengan Model Tanam Jajar Legowo - Feronika, Intan; Hidayat, Muhammad Syahrul; Laoli, Junirman; Rusdayani, Fina (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
One of the innovations to increase rice production is the system of rice intensification (SRI) and legowo jajar system. SRI is a one-seeded rice planting per planting hole. The double advantage will be obtained by farmers by practicing this SRI technology, because in addition to savings on production costs can also increase yields to be doubled. Legowo parallelogram system is a technique to manipulate spacing to improve rice yield so that there are many edge plants. The purpose of this activity is to provide innovation and increase farmer's awareness of SRI method with legowo javanese planting model for rice productivity in the Village Empat Balai of Kuok Subdistrict Kampar and increase rice productivity. The method used is the extension method and give the pre and post test questionnaires to the farmers. Based on the results of the questionnaire, this activity succeeded in increasing and increasing knowledge insight of farmers in Empat Balai village.